Damage analysis of concrete-filled square stainless steel columns based on acoustic emission and Markov chain methods. (15th April 2023) - Ma, Yuefei; Liu, Meiyu; Yang, Lu; Dai, Peng; Fan, Junwei
Highlights: Establishing a damage prediction model based on the Markov chain. Investigating the AE characteristics of the CFSST columns under compression. Characterizing the damage stages by AE energy and b -value analysis. Distinguishing the tensile and shear cracks of the CFSST columns by RA-AF analysis. Abstract: A test of concrete-filled square stainless steel (CFSST) columns with different eccentricities under compression was conducted to evaluate their failure and damage characteristics. Acoustic emission (AE) analysis was used to assess the damage process, and a damage prediction model based on the Markov chain was established. The monitoring results showed that the outward buckling was the dominant damage mode. As the eccentricity increased, the damage location changed from both sides of the column to the compressed side. The AE characteristic energy and b -value accurately described the damage process, which was divided into three stages: initial stability, cracking and buckling, and approaching failure. An analysis of the rise time/peak amplitude ratio (RA) and AE count/duration ratio (AF) indicated that tensile cracking was dominant in the three stages. A prediction model based on Markov chain was proposed to reflect state of CFSST columns, which could provide effective guidance in practical engineering.